Current Insights into the Modulation of Oral Bacterial Degradation of Dental Polymeric Restorative Materials - Zhang, Ning (Materials (Basel), 2017)
Dental polymeric composites have become the first choice for cavity restorations due to their esthetics and capacity to be bonded to the tooth. However, the oral cavity is considered to be harsh environment for a polymeric material. Oral biofilms can degrade the polymeric components, thus compromising the marginal integrity and leading to the recurrence of caries. Recurrent caries around restorations has been reported as the main reason for restoration failure. The degradation of materials greatly compromises the clinical longevity. This review focuses on the degradation process of resin composites by oral biofilms, the mechanisms of degradation and its consequences. In addition, potential future developments in the area of resin-based dental biomaterials with an emphasis on anti-biofilm strategies are also reviewed.